2019
DOI: 10.17826/cumj.461671
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between clinical severity of psoriasis and histopathological findings? a clinicopathological study

Abstract: Amaç: Psoriazis, şiddeti hastadan hastaya değişen yaygın bir kronik inflamatuar deri hastalığıdır. Bu çalışmada, histopatolojik bulgular ile hastalığın klinik şiddeti arasında ilişki olup olmadığını araştırmayı amaçladık.Gereç ve Yöntem: Bu retrospektif çalışmada, hem klinik hem de deri biyopsisi ile histopatolojik olarak psoriazis vulgaris tanısı konulan 51 olgu incelendi. Olguların parafin bloklarından hazırlanan kesitleri mikroskobik olarak incelendi ve bulgular çeşitli histopatolojik özellikler açısından k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It has been reported in the literature that there is no correlation between histopathological findings and PASI scores. 33,34 In their quantitative computer-aided study, Kim et al observed a relationship between histopathological findings and the three components of the PASI score (erythema, thickness, and desquamation). 35 In our study, stratum basale necrotic keratinocytes were observed at higher rates only in patients with high PASI values.…”
Section: Dermal Infiltrationmentioning
confidence: 99%
“…It has been reported in the literature that there is no correlation between histopathological findings and PASI scores. 33,34 In their quantitative computer-aided study, Kim et al observed a relationship between histopathological findings and the three components of the PASI score (erythema, thickness, and desquamation). 35 In our study, stratum basale necrotic keratinocytes were observed at higher rates only in patients with high PASI values.…”
Section: Dermal Infiltrationmentioning
confidence: 99%